A 262 MHz Narrow Band RF Transceiver for Korean M-Bus Smart Metering Service - Park, Dong-Wuk; Byeon, Ki-Ryun; Lee, Gi-Sung; Lim, Tae-Hee; Jo, Kyoung-Hwan; Oh, Tae Hyoun; Park, Hyung-Chul; Eo, Yun-Seong (Journal of semiconductor technology and science, 2024)
In this paper, a 262 MHz NB-IoT RF transceiver IC for Korean M-Bus smart metering service is presented. To mitigate the DC noise and 1/f noise near the narrow signal band and prevent SNR degradation caused by adjacent channel interference, low IF receiver with 4th order poly-phase filter is employed. The prototype is fabricated using the 0.18 μm CMOS process and has a size of 3.3 mm x 3.1 mm. It consumes 41.4/37.8 mW in transmit and receive modes, respectively. The measured results show that the maximum Tx power and OIP3 are +15.4/24 dBm and the receiver sensitivity is -105.4 dBm for PER 10-1 and 50-kbps GFSK modulation with 56 dBc ACR. The measured performance can provide the several-km communication distance for the smart monitoring sensors. KCI Citation Count: 0